Establishing Safety and Stability for Enhanced Treatment Engagement With the Unified Protocol: A Case Study. (December 2020) - Mian, Maha N.; Lin, Betty; Hormes, Julia M.; Earleywine, Mitch
Despite the vast array of empirically validated treatments for psychopathological problems, interventions still require considerable client resources for engagement and success. For clients lacking safety and stability outside of therapy, numerous barriers to treatment can prevent improvement and lead to disengagement. In such cases, therapists can seek to understand clients' difficulties with safety and stability. Developing both rapport and the client's problem-solving abilities can instill a sense of agency, keeping clients in treatment for better outcomes overall. This case study describes the modified application of the Unified Protocol following safety planning and crisis management. "Mary, " a 23-year old female, presented to a training clinic with fluctuating mood episodes, trauma symptoms, and problem substance use; pre, post, and routinely collected session data with clinical report indicate symptom improvement and increased treatment engagement following client gains in safety, employment, and housing. This case illustrates the importance of the therapeutic alliance in establishing client safety to effectively deliver a transdiagnostic treatment to address core mechanisms underlying emotion dysregulation.